Plan de marketing para almacén “Don Boli”, en el cantón El Empalme, periodo 2015 - Giler Reasco, Jenny Fabiola (2016)
The importance of this research lies in developing a marketing plan to store "Don Boli", in the village of El Empalme. In the project discussed in chapter one, the current situation of the store to see how well the appliance store operates in the market of the joint and to take on an improvement plan; Chapter Two conceptual and reference framework developed by documenting information to have a profound knowledge of theory related to the objectives of this research, in chapter three methods, types and technical research were identified, in addition to determining the target population by applying the relevant procedures whereby establish the research findings; Chapter four presents the results obtained from market research interviews were conducted where the owner of the store and customers of the same practices and consumption of the products were determined, strategies and plan of action to be identified making decisions according to changes that may occur in the business environment. The budget for implementation of the marketing plan was developed. Then in chapter five relevant conclusions and appropriate recommendations, and finally in chapter six the literature is reflected.